2016
DOI: 10.1002/cbdv.201500514
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting Anticancer Compounds in Actinomycetes Recovered from the Sediments of Saint Peter and Saint Paul's Archipelago, Brazil

Abstract: Saint Peter and Saint Paul's Archipelago is a collection of 15 islets and rocks remotely located in the equatorial Atlantic Ocean. In this particular site, the present project intended to assess the biodiversity and biotechnological potential of bacteria from the actinomycete group. This study presents the first results of this assessment. From 21 sediment samples, 268 strains were isolated and codified as BRA followed by three numbers. Of those, 94 strains were grown in liquid media and submitted to chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
(26 reference statements)
1
17
0
3
Order By: Relevance
“…The cytotoxic activity evaluation of the ethyl acetate extract obtained from each strain showed that 26 crude extracts were considered cytotoxic at 50 µg/mL (Figure 1a), while nine were also active at 5 µg/mL (Figure 1b). These numbers are similar to those obtained from other studies performed with marine bacteria recovered from sediments collected at Atlantic islands [20,21]. In a previous work that investigated culturable actinomycetes isolated from sediments collected at the Saint Peter and Saint Paul Archipelago, 268 strains were isolated from 21 sediment samples, while 94 strains were selected for cytotoxicity analysis of their crude extract against HCT-116 cell lines [20].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The cytotoxic activity evaluation of the ethyl acetate extract obtained from each strain showed that 26 crude extracts were considered cytotoxic at 50 µg/mL (Figure 1a), while nine were also active at 5 µg/mL (Figure 1b). These numbers are similar to those obtained from other studies performed with marine bacteria recovered from sediments collected at Atlantic islands [20,21]. In a previous work that investigated culturable actinomycetes isolated from sediments collected at the Saint Peter and Saint Paul Archipelago, 268 strains were isolated from 21 sediment samples, while 94 strains were selected for cytotoxicity analysis of their crude extract against HCT-116 cell lines [20].…”
Section: Introductionsupporting
confidence: 84%
“…In a previous work that investigated culturable actinomycetes isolated from sediments collected at the Saint Peter and Saint Paul Archipelago, 268 strains were isolated from 21 sediment samples, while 94 strains were selected for cytotoxicity analysis of their crude extract against HCT-116 cell lines [20]. Among them, 26 strains produced cytotoxic extracts, and the chemical analysis by liquid chromatography-mass spectrometry (HPLC-MS/MS) suggested the production of known cytotoxic compounds, such as staurosporines and piericidins [20].…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS/MS combined with UV data and database analyses are used to confirm the structure of compounds of interest ( Ferreira et al, 2016 ). A variety of diketopiperazines from strain 452 T were detected using LC-MS/MS and analyzed by comparing with data in the Human Metabolome Database 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Among culturable actinobacteria isolated from sediments collected therein, 268 strains were isolated and 94 were tested for cytotoxicity of their extracts, from which 26 produced cytotoxic extracts. Chemical analysis by HPLC-MS/MS suggested the production of known cytotoxic compounds, such as staurosporines and piericidins and, interestingly, saliniketals and rifamycins [150]. The latter class of compounds are typical natural products synthesized by bacteria of the Salinispora genus.…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 99%
“…Another strain recovered from the SPSPA that gave a cytotoxic extract, Streptomyces sp. BRA199, was subjected to a bioassayguided fractionation to yield piericidin A and 3 diketopiperazines [150]. Although the first compound was not particularly assessed therein for bioactivity, piericidins are widely known as potent cytotoxins, originally isolated from actinobacteria, especially from Streptomyces sp.…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 99%